2010
DOI: 10.1038/ki.2010.170
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of mycophenolic acid in severe lupus nephritis

Abstract: Mycophenolic acid (MPA) is an effective treatment for active lupus nephritis despite its variable efficacy in different ethnic groups. Here we tested whether pharmacokinetic monitoring may help to optimize dosing of MPA in an Asian population. Patients with biopsy-proven class III or IV lupus nephritis (ISN/RPS category) were treated with mycophenolate mofetil or enteric-coated mycophenolate sodium. One month after initiating treatment we measured plasma MPA levels in eight samples taken over a 12-h period aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 32 publications
6
76
3
Order By: Relevance
“…The finding of higher total MPA AUC(0,12 h) in all responders is consistent with the results of a previous investigation involving patients with lupus nephritis (65.98 ± 23.77 vs. 32.08 ± 7.97 mg l -1 h) [8]. A significantly higher total MPA AUC(0,8 h) was also observed in all responders.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The finding of higher total MPA AUC(0,12 h) in all responders is consistent with the results of a previous investigation involving patients with lupus nephritis (65.98 ± 23.77 vs. 32.08 ± 7.97 mg l -1 h) [8]. A significantly higher total MPA AUC(0,8 h) was also observed in all responders.…”
Section: Discussionsupporting
confidence: 81%
“…The analyses evaluated drug exposures in relation to treatment response since starting MPA and drugrelated adverse events. [7][8][9][10][11][12][13][14][15][16][17][18][19] was observed in patients with lowest tertile exposure to both total MPA and prednisolone as compared with patients with middle and higher tertile exposure (17% vs. 74%, P = 0.023). …”
mentioning
confidence: 83%
“…As exposure to prednisone and MF was comparable between the two groups of patients, dose does not seem to affect the responses. Pharmacokinetic monitoring of mycophenolic acid has traditionally received little attention; however, findings in this area have recently become available [33]. Therefore, most participating centers in our study did not monitor serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…The results also highlighted the importance of socioeconomic issues in health care access and delivery in Asian countries. Also, studies in Thai patients have shown that there was a marked interindividual difference in MPA metabolism and that drug exposure was related to therapeutic response [73,74]. In this regard, there are ongoing studies on the pharmacokinetics and pharmacogenomics of MPA in different Asian populations.…”
Section: Discussionmentioning
confidence: 99%